Peran Kepemimpinan Tokoh Agama Dalam Meningkatkan Sikap Keberagamaan Masyarakat Di Desa Sangowo Kecamatan Morotai Timur Kabupaten Pulau Morotai - Posu, Risaldi; Tasik, Femmy; Goni, Shirley (AGRI-SOSIOEKONOMI, 2023)
The purpose of this study was to find out how the leadership role of religious leaders in improving the religious attitude of the community in Sangowo Village, East Morotai District. The research was conducted from February to April 2022. The research was conducted in Sangowo Village, East Morotai District, Morotai Island Regency. This research uses a descriptive method with a qualitative approach. The focus of this research is the leadership role of religious leaders in increasing the attitude of diversity in society. Data was collected through observation techniques, interviews and documentation. The results of the study show that the role of religious leaders aims to increase community diversity which is still lacking because from the author's observation that in general in Sangowo Village, East Morotai District, Morotai Island Regency there are still many people who preoccupy themselves with working only in world affairs so they forget about religious affairs.